2022
DOI: 10.1128/spectrum.01098-22
|View full text |Cite
|
Sign up to set email alerts
|

DDX5/METTL3-METTL14/YTHDF2 Axis Regulates Replication of Influenza A Virus

Abstract: The replication and transcription of influenza virus depends on the participation of many host factors in cells. Exploring the relationship between viruses and host factors will help us fully understand the characteristics and pathogenic mechanisms of influenza viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Previous study has reported that METTL3 impedes the degradation of IRAKM, a key negative regulator of TLR4, consequently leading to the suppression of TLR4 and its associated downstream signaling pathways [ 47 ]. METTL14 collaborates with METTL3 in regulating the replication of various viruses, including HCV [ 48 ], HDV [ 49 ], IAV [ 50 ], HSV-1 [ 51 ] and HIV [ 52 ], suggesting a supporting role for METTL14 in these viral infections. However, in the case of viruses like PCV2 [ 53 ], PRV [ 54 ], VSV [ 55 ], and EBV [ 24 ], METTL14 is shown to play a crucial role in promoting their replication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has reported that METTL3 impedes the degradation of IRAKM, a key negative regulator of TLR4, consequently leading to the suppression of TLR4 and its associated downstream signaling pathways [ 47 ]. METTL14 collaborates with METTL3 in regulating the replication of various viruses, including HCV [ 48 ], HDV [ 49 ], IAV [ 50 ], HSV-1 [ 51 ] and HIV [ 52 ], suggesting a supporting role for METTL14 in these viral infections. However, in the case of viruses like PCV2 [ 53 ], PRV [ 54 ], VSV [ 55 ], and EBV [ 24 ], METTL14 is shown to play a crucial role in promoting their replication.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the DDX5 protein is a multifunctional DEAD-box RNA helicase and a transcription cofactor that participates in a variety of cellular activities across species ( Nyamao et al, 2019 ). Previous studies have additionally demonstrated that DDX5 is involved in a variety of clinical diseases ( Ariumi, 2022 ; Zhang et al, 2022 ; Zhao et al, 2022 ), especially carcinogenesis and the development of cancer ( Zheng et al, 2021 ; Le et al, 2022 ). The common molecular pathways involved in the function of DDX5 in carcinogenesis remain to be thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting m6A not only mediates the control of the innate immune response but also blocks the replication of several viruses, including SARS-CoV-2 and influenza A virus ( 149 , 150 ). The cytosolic m6A-binding proteins YTHDF1, YTHDF2, and YTHDF3 undergo phase separation ( 151 155 ); however, the association between the LLPS and the function of YTHDF proteins remains to be confirmed.…”
Section: Roles Of Llps Condensation During Innate Antiviral Immunitymentioning
confidence: 99%